FAKTOR KOMORBID YANG MEMPENGARUHI KEJADIAN KEMATIAN PASIEN COVID-19 DI RUMAH SAKIT RSU. ROYAL PRIMA TAHUN 2021 - Siregar, Resisca; Sinatra, Jadeny; Surjani, Lylys (Universitas Methodist Indonesia, 2024)
Background. Corona Virus Disease-19, also known as COVID-19, is a disease caused by the Severe Acute Respiratory Syndrome Corona Virus-2 (SARS-CoV-2). COVID-19 became a pandemic outbreak determined by the World Health Organization (WHO) on December 31, 2019, which first occurred in Wuhan, China. Indonesia itself confirmed the first case on March 2, 2020. As of January 2, 2022, the government of the Republic of Indonesia has reported 4,263,168 confirmed cases of COVID-19. There have been around 144,097 reported COVID-19-related deaths. One of the causes of death is the presence of comorbidities. The presence of a history of comorbidities increases the severity leading to death. Research Objectives: To find out the relationship between one comorbid, namely HT, DM or Heart with COVID-19 at the Hospital which can cause death and to find out the relationship between two comorbids, namely HT with DM or HT with Heart or DM with Heart with COVID-19 at home. Illness that can lead to death Results: The results found were that there was a relationship between the type of comorbidity and the number of deaths in COVID-19 patients, this was based on a bivariate statistical test using the chi-square test, p value <0.05. This shows that there is a significant relationship between the type of comorbidity and the number of comorbidities on the severity of patients with confirmed COVID-19. Conclusion: The results of this study show that comorbidities are one of the factors that play a role in causing severity in COVID-19 patients and even death. The most common comorbidities were HT, DM for single comorbid and for multiple comorbids were DM with HT, DM with heart.